A heat and moisture-exchanging mask impairs self-paced maximal running performance in a sub-zero environment - Tutt, A. S.; Persson, H.; Andersson, E. P.; Ainegren, M.; Stenfors, N.; Hanstock, H. G. (European Journal of Applied Physiology, 2021)
Heat-and-moisture exchanging devices (HME) are commonly used by winter endurance athletes during training in sub-zero environments, but their effect on performance is unknown. This study aimed to investigate the effect of an HME on running performance at -15°C in healthy people. Twenty-three healthy adults (15 male, 8 female; age 18-53 y; VO2peak men 56 ± 7, women 50 ± 4 mL/kg·min) performed two treadmill exercise tests with and without HME in a randomized, crossover design. Participants performed a 30-min submaximal warm-up (SUB), followed by a 4-min maximal, self-paced running time-trial (TT). Heart rate (HR) and respiratory frequency (fR) were monitored using a chest strap; muscle oxygenation (SmO2) and deoxyhemoglobin concentration ([HHb]) were derived from wireless near-infrared-spectroscopy sensors on m. vastus lateralis; blood lactate was measured 2-min before and after the maximal test. HME reduced distance covered in the TT by 1.4% (p = 0.033), despite similar perceived exertion, HR, fR and lactate accumulation. The magnitude of the effect of the HME on performance was associated with body mass (r2 = 0.22, p = 0.027), but not aerobic fitness or maximal ventilation. SmO2 and [HHb] were lower (-3.1%, p < 0.001) and higher (0.35 AU, p < 0.001), respectively, during the TT with HME. HR was 2.7 beats·min-1 higher during SUB with HME (p < 0.001). In the male participants, SmO2 was lower (-3.8%, p < 0.001) and [HHb] higher (0.42 AU, p < 0.001) during SUB with HME. Our findings suggest that HME usage impairs maximal running performance and increases the physiological demands of submaximal exercise.